On the characterization of a new type of oxide-confined 850nm GaAs-based vertical-cavity surface-emitting laser - MITANI, S; CHOUDHURY, P; ALIAS, M (ELSEVIER GMBH, 2008)
Using simulation tools, results are presented for a new type of oxide-confined vertical-cavity surface-emitting laser (VCSEL) to be operated at 850 nm region of the electromagnetic spectrum. The structural details for the device are illustrated. The novelty of the device lies in that the low-doped DBR layers as well as the barrier reduction layers within the DBRs are introduced for the device fabrication, which finally provide much better efficiency of the proposed VCSEL structure. Simulations have been performed for the analyses of several features of the VCSEL that primarily govern the operational characteristics of the device. A very small deviation from the proposed structure will essentially affect the features of the output light. (C) 2007 Elsevier GmbH. All rights reserved.